Pyrogenic Carbon Increases Pitch Pine Seedling Growth, Soil Moisture Retention, and Photosynthetic Intrinsic Water Use Efficiency in the Field - Licht, Jeff; Smith, Nicholas G. (Frontiers in Forests and Global Change, 2020)
ABSTRACT Climate change and land management are altering forest fire frequency and intensity worldwide. In some Northeast U.S. forests, pitch pine (Pinus rigida Miller) is not suffering from presence but rather a lack of wildfire events. In their absence, prescribed fire is being used to diminish fuel loads, open canopies and reduce competition. Pyrogenic carbon (PyC) produced by the fires may also improve soil moisture retention and plant physiological processes. Where the application of prescribed fire is not feasible due to nearby human populations, we reason prescribed fire PyC could be replaced by anthropogenic PyC product to provide similar soil benefits. We tested this hypothesis with pitch pine seedlings at a site absent overstory planted in submerged tree pots with control and PyC-imbued soils. Investigators found anthropogenic and forest PyC fostered similar growth, soil moisture retention and photosynthetic intrinsic water use efficiency, both significantly higher than unamended soils. We conclude anthropogenic subsurface PyC soil amendment provides a conservation management tool for enhancing benefits in ecosystems where prescribed fire is not a viable option in northerly forests in the U.S.